A molybdenum-based composite material and its preparation and application

The self-supporting structure of molybdenum-based composite materials and multi-layer stacked oxides are prepared in combination with chemical vapor deposition methods, which solves the problems of high cost of existing electrocatalysts and prone to inactivation, achieving low cost and high efficiency Hydrogen-based hydrogen fuel electrolytic hydrolysis effect.

CN115874138BActive Publication Date: 2025-01-10FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210226648.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-27
Filing Date
2022-03-09
Publication Date
2025-01-10
Estimated Expiration
2042-03-09

AI Technical Summary

Technical Problem

Existing electrocatalysts are costly at high current density, difficult to synthesize on a large scale, and are prone to deactivation of catalytic activity, limiting the industrial application of hydrogen fuels.

Method used

Molybdenum-based composite materials, including MoO2 and MoP, were prepared by a self-supported molybdenum substrate and multi-layer stacked molybdenum oxide structure in combination with chemical vapor deposition methods to form a highly active hydrogen evolution electrode and restore catalytic activity through simple repair technology.

Benefits of technology

It realizes the preparation of low-cost and high-efficiency catalysts, can work for a long time under high current density and high alkali concentration conditions, has anti-short circuit and open-circuit oxidation properties, and can be re-repaired to reduce raw material losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115874138B_ABST
    Figure CN115874138B_ABST
Patent Text Reader

Abstract

The present application discloses a molybdenum-based composite material and its preparation and application, characterized in that it includes MoO2, MoP and a Mo substrate; the MoO2 and the MoP grow on the Mo substrate. The composite material, thanks to the three-dimensional structure of the precursor molybdenum-based oxide, has a relatively large specific surface area, which is beneficial to increase the active sites of the catalyst; the composite material directly generates the precursor by in-situ reaction through a chemical vapor deposition method, forming a seamless electrode device structure; the prepared seamless molybdenum-based electrode device can not only fully expose the active sites of the molybdenum-based compound catalyst, but also help accelerate the transfer of charges, thereby improving the activity of the catalyst; the preparation method can determine the degree of phosphating by adjusting different annealing temperatures, thereby improving the catalytic activity of the catalyst itself; and it has the advantages of simple operation, stable reaction and strong controllability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a molybdenum-based composite material and its preparation and application, belonging to the technical field of water electrolysis and hydrogen evolution. Background Art

[0002] Hydrogen (H 2 ) is considered a promising alternative to natural fossil fuels due to its high energy density, abundant reserves, high efficiency and cleanliness. Water electrolysis is considered to be one of the most feasible and economical methods to generate hydrogen from sustainable energy sources such as solar and wind power. Alkaline water electrolysis is currently the most widely used hydrogen production technology in industry, with the advantages of safety, reliability, long service life and superior economic benefits. To date, platinum group metals (PGMs) are still the most efficient electrocatalytic materials, but the high cost and limited reserves of precious metals on the earth limit the further commercial development and widespread application of platinum group metals. In recent years, transition metal compounds such as metal sulfides, selenides, phosphides, nitrides, carbides and metal alloys have received a lot of attention.

[0003] In recent years, despite great progress in developing earth-abundant catalysts that perform comparable to commercial Pt / C electrodes at high current densities, there are still major challenges in bringing these promising hydrogen evolution electrodes to large-scale practical applications. The main problem is that the total cost of the electrocatalyst, i.e., the cost of the raw materials and the preparation process, is too high. Due to the complex operating steps and sensitive conditions (e.g., high pressure and vacuum), the synthetic routes for hydrogen evolution electrodes reported so far are energy-intensive and difficult to synthesize on a large scale. In addition, when these catalysts are deactivated, they are almost impossible to repair, resulting in a loss of raw materials. With the increasing demand for hydrogen fuel, the problem of low yield becomes more serious. Currently in industry, nickel-based alloys are one of the electrocatalysts used for alkaline hydrogen evolution, but they are not very effective at high current densities (e.g., 500 mA / cm 2 ) still requires a fairly high overpotential, resulting in energy loss. Therefore, there is an urgent need to develop low-cost and efficient catalysts with high current density for large-scale use. Summary of the invention

[0004] According to one aspect of the present application, a molybdenum-based composite material is provided. The molybdenum-based composite material has a self-supporting structure, wherein the molybdenum substrate is a substrate that plays a self-supporting role and is also a molybdenum source; the molybdenum-based oxide is stacked together in multiple layers and aggregated and grown at different angles on the surface of the smooth molybdenum substrate.

[0005] A molybdenum-based composite material comprising MoO 2 , MoP and Mo substrate;

[0006] The MoO 2 and the MoP is grown on the Mo substrate.

[0007] Optionally, the MoO 2 And the MoP has a layered structure.

[0008] The MoO 2 The MoP is stacked together in multiple layers and grows in aggregate at different angles.

[0009] Optionally, the MoO 2 The mass ratio of the MoP is 9:1 to 1:1.

[0010] Optionally, the MoO 2 The mass ratio of the MoP to the MoP is independently selected from any value of 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, or any range therebetween.

[0011] Optionally, the MoO 2 - In MoP, the content of MoP is 10% to 50%.

[0012] Optionally, the thickness of the Mo substrate is 0.1 mm to 1 mm;

[0013] Preferably, the Mo substrate has a thickness of 0.15 mm to 0.25 mm.

[0014] Optionally, the thickness of the Mo substrate is independently selected from any value among 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, or any range therebetween.

[0015] Optionally, the MoO 2 and the thickness of the MoP is 10 μm to 30 μm;

[0016] Preferably, the MoO 2 The MoP has a thickness of 15 μm to 20 μm.

[0017] Optionally, the MoO 2 and the thickness of the MoP is independently selected from any value of 10 μm, 12 μm, 15 μm, 17 μm, 20 μm, 22 μm, 25 μm, 27 μm, 30 μm, or any range therebetween.

[0018] Optionally, the MoO 2 And the specific surface area of ​​the MoP is 0.2m 2 ~2m 2 ;

[0019] Preferably, the MoO 2and the specific surface area of ​​the MoP is 0.3m 2 ~0.5m 2 .

[0020] Optionally, the MoO 2 and the specific surface area of ​​the MoP is independently selected from 0.2 m 2 、0.4m 2 、0.6m 2 、0.8m 2 , 1m 2 , 1.2m 2 、1.4m 2 、1.6m 2 、1.8m 2 , 2m 2 Any value in between or any range of values ​​between them.

[0021] According to yet another aspect of the present application, a method for preparing a molybdenum-based composite material is provided.

[0022] A method for preparing a molybdenum-based composite material comprises the following steps:

[0023] (S1) Reaction I on molybdenum foil to obtain MoO 3 film;

[0024] (S2) Place MoO 3 After annealing reduction, MoO 2 ;

[0025] (S3) Place red phosphorus upstream of the circulating airflow and MoO 2 Reaction II, MoO 2 -MoP / Mo composite materials.

[0026] Optionally, the molybdenum foil is pretreated before reaction I, comprising the following steps: immersing the molybdenum foil in an acid solution, and then removing surface oil stains by heated acetone.

[0027] Optionally, the MoO 3 The film is a three-dimensional structure.

[0028] Optionally, the mass of the red phosphorus is 0.05g to 0.2g.

[0029] Optionally, the mass of the red phosphorus is independently selected from any value among 0.05g, 0.08g, 0.1g, 0.12g, 0.15g, 0.17g, 0.2g or any range value therebetween.

[0030] Optionally, the conditions of reaction I in step (S1) are as follows:

[0031] The insulation temperature is 650℃~700℃;

[0032] The insulation time is 30min to 120min.

[0033] Optionally, the insulation temperature is independently selected from any value of 650° C., 660° C., 670° C., 680° C., 690° C., 700° C., or any range therebetween.

[0034] Optionally, the holding time is independently selected from any value among 30 min, 50 min, 60 min, 80 min, 90 min, 100 min, 110 min, 120 min, or any range value between two of them.

[0035] Optionally, the heating rate is 10°C / min to 40°C / min.

[0036] Optionally, the heating rate is independently selected from any value of 10°C / min, 15°C / min, 20°C / min, 25°C / min, 30°C / min, 35°C / min, 40°C / min, or any range therebetween.

[0037] Optionally, the reaction atmosphere is an oxygen-containing atmosphere.

[0038] Optionally, before annealing and reduction in step (S2), the vacuum is evacuated to 1 Torr to 5 Torr and then filled with argon gas.

[0039] Optionally, the annealing reduction conditions are as follows:

[0040] The insulation temperature is 600℃~750℃;

[0041] The insulation time is 30min to 60min.

[0042] Optionally, the insulation temperature is independently selected from any value of 600°C, 620°C, 650°C, 680°C, 700°C, 720°C, 740°C, 750°C, or any range therebetween.

[0043] Optionally, the holding time is independently selected from any value among 0 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, or any range value between two of them.

[0044] Optionally, the heating rate is 10°C / min to 40°C / min.

[0045] Optionally, the heating rate is independently selected from any value of 10°C / min, 15°C / min, 20°C / min, 25°C / min, 30°C / min, 35°C / min, 40°C / min, or any range therebetween.

[0046] Optionally, the reaction atmosphere is a mixture of argon and hydrogen.

[0047] Optionally, the flow ratio of hydrogen to argon is 1:1 to 1:3.

[0048] Optionally, before reaction II in step (S3), the vacuum is evacuated to 1 Torr to 5 Torr and then filled with argon.

[0049] Optionally, the conditions of reaction II in step (S3) are as follows:

[0050] The insulation temperature is 500℃~900℃;

[0051] The insulation time is 10min to 60min.

[0052] Optionally, the holding temperature is independently selected from any value of 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, or any range therebetween.

[0053] Optionally, the holding time is independently selected from any value among 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, or any range value therebetween.

[0054] Optionally, the heating rate is 10°C / min to 40°C / min.

[0055] Optionally, the heating rate is independently selected from any value of 10°C / min, 15°C / min, 20°C / min, 25°C / min, 30°C / min, 35°C / min, 40°C / min, or any range therebetween.

[0056] Optionally, the reaction atmosphere is a mixture of argon and hydrogen.

[0057] Optionally, the flow ratio of hydrogen to argon is 1:1 to 1:3.

[0058] Optionally, in step (S2) or (S3), the total amount of argon and hydrogen used is 100 sccm.

[0059] Optionally, in step (S2) or (S3), the amount of argon and hydrogen is H 2 (25sccm)+Ar(75sccm),H 2 (40sccm)+Ar(60sccm) or H 2 (50sccm)+Ar(50sccm).

[0060] According to the third aspect of the present application, a molybdenum-based composite material is provided as a cathode catalyst for hydrogen evolution. When the molybdenum-based composite material is used as a catalyst, when the electrode activity decreases, the original hydrogen evolution activity can be restored by a simple repair technology, thereby reducing the cost of the electrode raw materials. The prepared highly active hydrogen evolution electrode has a more superior activity under high alkali concentration conditions, and can work for a long time under harsh conditions such as high temperature and high current density, and also has special properties such as resistance to short circuit and resistance to open circuit oxidation.

[0061] The molybdenum-based composite material described above and / or the molybdenum-based composite material obtained by the preparation method described above is used as a hydrogen evolution cathode catalyst.

[0062] The beneficial effects of this application include:

[0063] 1) A molybdenum-based composite material provided in the present application has a relatively large specific surface area due to the three-dimensional structure of the precursor molybdenum-based oxide, which is beneficial to increase the active sites of the catalyst; the molybdenum-based composite material directly generates a precursor through an in-situ reaction by a chemical vapor deposition method, forming a seamless electrode device structure; the prepared seamless molybdenum-based electrode device can not only fully expose the active sites of the molybdenum-based compound catalyst, but also help accelerate the transfer of charges, thereby improving the activity of the catalyst.

[0064] 2) The method for preparing a molybdenum-based composite material provided in the present application can determine the degree of phosphating by adjusting different annealing temperatures, thereby improving the catalytic activity of the catalyst itself; and it has the advantages of simple operation, stable reaction, and strong controllability. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 A flow chart and optical photographs of samples for preparing active cathode hydrogen evolution catalysts for diaphragm electrolyzers in the chlor-alkali industry for this application (Figure a is the preparation flow chart, and Figures b and c are optical photographs of molybdenum foil and electrodes).

[0066] Figure 2 MoO prepared in Example 1 of the present application 3 Scanning electron microscope image of MoO 3 Scanning electron microscope image, b is MoO 3 Scanning electron microscope image at high magnification.

[0067] Figure 3 MoO prepared in Example 1 of the present application 2 -X-ray diffraction pattern of MoP composite catalyst.

[0068] Figure 4 MoO prepared in Example 1 of the present application 2-Scanning electron microscope images of MoP composite material catalyst, where a, b, and c are scanning electron microscope images at different magnifications, respectively.

[0069] Figure 5 MoO prepared in Example 1 of the present application 2 -X-ray photoelectron spectroscopy of MoP composite catalysts.

[0070] Figure 6 MoO prepared in Example 1 of the present application 2 -Schematic diagram of the performance test of hydrogen evolution by water electrolysis using MoP / Mo composite material electrode.

[0071] Figure 7 MoO prepared in Example 1 of the present application 2- LSV (linear sweep voltammetry) curve of hydrogen evolution in water electrolysis using MoP / Mo composite electrode.

[0072] Figure 8 MoO prepared in Example 1 of the present application 2 -Tafel plot (Tafel slope) curve of hydrogen evolution in water electrolysis using MoP / Mo composite electrode.

[0073] Fig. 9 MoO prepared in Example 1 of the present application 2 -Stability curve of hydrogen evolution in water electrolysis using MoP / Mo composite electrode. DETAILED DESCRIPTION

[0074] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0075] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels, among which the tube furnace was purchased from Hefei Kejing Materials Co., Ltd. (OTF-1200X);

[0076] The nitrogen gun was purchased from Shenzhen Jingliang Technology Co., Ltd.;

[0077] Molybdenum foil was purchased from Aladdin Chemical Reagent Co., Ltd.

[0078] The analysis method in the examples of this application is as follows:

[0079] The samples were analyzed by scanning electron microscope (HITACHI UHR FE-SEM SU8010).

[0080] XRD analysis was performed using an X-ray diffractometer (D8 ADVANCE).

[0081] XPS analysis was performed using an X-ray photoelectron spectroscopy (ESCALAB 250Xi).

[0082] The electrochemical performance was analyzed using a CHI600E electrochemical workstation.

[0083] Example 1

[0084] Step 1: First, sand off the oxide layer on the surface of the molybdenum foil with sandpaper, and then place the polished molybdenum foil in hydrochloric acid and hot acetone (80°C) in turn, soak for 30 minutes to remove surface oil. After rinsing with deionized water, ultrasonic cleaning is performed in anhydrous ethanol for 30 minutes, and finally blown dry with a nitrogen gun for use. The dried molybdenum foil is placed in a tubular furnace and heated to 700°C at a heating rate of 10°C / min in an air atmosphere for 120 minutes, and then a thick layer of three-dimensional molybdenum-based oxide structure is formed on the surface of the molybdenum foil.

[0085] The surface morphology of the annealed molybdenum foil was analyzed by field emission scanning electron microscopy. Figure 2 As shown in the figure, it can be clearly seen that the smooth surface of the molybdenum foil has been covered by the formed molybdenum-based oxide, and the original flat substrate is almost invisible. The large blocks of molybdenum-based oxide are stacked together disorderly and oxidized and grown at a certain angle on the surface of the molybdenum foil. In order to further observe the growth morphology of the molybdenum-based oxide, the high-power scanning electron microscope was used to observe ( Figure 2 b), it was found that large blocks of molybdenum-based oxide grew vertically on the surface of the molybdenum foil, and the molybdenum-based oxide was stacked together in multiple layers, growing in clusters at different angles. Its thickness was about 5 microns, and the surface of the blocky molybdenum-based oxide was relatively smooth.

[0086] Step 2: According to the principle of thermal reduction reaction, the three-dimensional molybdenum-based oxide prepared above is placed in a cleaned ceramic boat and placed in a tube furnace. Before heating the tube furnace, the tube furnace is first closed and evacuated to about 1 Torr, and then filled with argon to remove the residual gas in the quartz tube. Then the tube furnace is quickly heated to 700°C within 30 minutes and the reaction temperature is maintained for 30 minutes. During this annealing reduction process, a mixed gas of argon and hydrogen is always passed through with a flow rate of Ar:H 2 =60:40, and then cooled naturally to room temperature, the obtained sample is molybdenum dioxide. The obtained sample is subjected to X-ray diffraction analysis, and the results are as follows Figure 3 As shown, the sample was confirmed to be molybdenum dioxide.

[0087] Step 3: Prepare the MoO 2Place it in a cleaned ceramic boat, and place it downstream of the tube furnace. The ceramic boat loaded with 0.08g of red phosphorus is placed upstream of the tube furnace. Before heating the tube furnace, first close the tube furnace, evacuate it to about 1Torr, and then fill the tube furnace with argon to remove the residual gas in the quartz tube. Then quickly heat the tube furnace to 700℃ within 30min, and maintain the reaction temperature for 30min. During this phosphating process, a mixed gas of argon and hydrogen is always passed through with a flow rate of Ar:H 2 =60:40, and then cooled naturally to room temperature. The obtained sample is MoO 2 -MoP composite catalyst.

[0088] Example 2

[0089] Step 1: First, sand off the oxide layer on the surface of the molybdenum foil with sandpaper, and then place the polished molybdenum foil in hydrochloric acid and hot acetone (80°C) in turn, soak for 30 minutes to remove surface oil. After rinsing with deionized water, ultrasonic cleaning is performed in anhydrous ethanol for 30 minutes, and finally blown dry with a nitrogen gun for use. The dried molybdenum foil is placed in a tubular furnace and heated to 700°C at a heating rate of 10°C / min in an air atmosphere for 120 minutes, and then a thick layer of three-dimensional molybdenum-based oxide structure is formed on the surface of the molybdenum foil.

[0090] Step 2: According to the principle of thermal reduction reaction, the three-dimensional molybdenum-based oxide prepared above is placed in a cleaned ceramic boat and placed in a tube furnace. Before heating the tube furnace, the tube furnace is first closed and evacuated to about 1 Torr, and then filled with argon to remove the residual gas in the quartz tube. Then the tube furnace is quickly heated to 700°C within 30 minutes and the reaction temperature is maintained for 30 minutes. During this annealing reduction process, a mixed gas of argon and hydrogen is always passed through with a flow rate of Ar:H 2 =60:40, and then naturally cooled to room temperature, and the obtained sample was molybdenum dioxide.

[0091] Step 3: Prepare the MoO 2 Place it in a cleaned ceramic boat, and place it downstream of the tube furnace. The ceramic boat loaded with 0.08g of red phosphorus is placed upstream of the tube furnace. Before heating the tube furnace, first close the tube furnace, evacuate it to about 1Torr, and then fill the tube furnace with argon to remove the residual gas in the quartz tube. Then quickly heat the tube furnace to 600℃ within 30min, and maintain the reaction temperature for 30min. During this phosphating process, a mixed gas of argon and hydrogen is always passed through with a flow rate of Ar:H 2 =60:40, and then cooled naturally to room temperature. The obtained sample is MoO 2 -MoP composite catalyst.

[0092] Example 3

[0093] Step 1: First, sand off the oxide layer on the surface of the molybdenum foil with sandpaper, and then place the polished molybdenum foil in hydrochloric acid and hot acetone (80°C) in turn, soak for 30 minutes to remove surface oil. After rinsing with deionized water, ultrasonic cleaning is performed in anhydrous ethanol for 30 minutes, and finally blown dry with a nitrogen gun for use. The dried molybdenum foil is placed in a tubular furnace and heated to 700°C at a heating rate of 10°C / min in an air atmosphere for 120 minutes, and then a thick layer of three-dimensional molybdenum-based oxide structure is formed on the surface of the molybdenum foil.

[0094] Step 2: According to the principle of thermal reduction reaction, the three-dimensional molybdenum-based oxide prepared above is placed in a cleaned ceramic boat and placed in a tube furnace. Before heating the tube furnace, the tube furnace is first closed and evacuated to about 1 Torr, and then filled with argon to remove the residual gas in the quartz tube. Then the tube furnace is quickly heated to 700°C within 30 minutes and the reaction temperature is maintained for 30 minutes. During this annealing reduction process, a mixed gas of argon and hydrogen is always passed through with a flow rate of Ar:H 2 =60:40, and then naturally cooled to room temperature, and the obtained sample was molybdenum dioxide.

[0095] Step 3: Prepare the MoO 2 Place it in a cleaned ceramic boat, and place it downstream of the tube furnace. The ceramic boat loaded with 0.08g of red phosphorus is placed upstream of the tube furnace. Before heating the tube furnace, first close the tube furnace, evacuate it to about 1Torr, and then fill the tube furnace with argon to remove the residual gas in the quartz tube. Then quickly heat the tube furnace to 800℃ within 30min, and maintain the reaction temperature for 30min. During this phosphating process, a mixed gas of argon and hydrogen is always passed through with a flow rate of Ar:H 2 =60:40, and then cooled naturally to room temperature. The obtained sample is MoO 2 -MoP composite catalyst.

[0096] Example 4

[0097] Step 1: First, sand off the oxide layer on the surface of the molybdenum foil with sandpaper, and then place the polished molybdenum foil in hydrochloric acid and hot acetone (80°C) in turn, soak for 30 minutes to remove surface oil. After rinsing with deionized water, ultrasonic cleaning is performed in anhydrous ethanol for 30 minutes, and finally blown dry with a nitrogen gun for use. The dried molybdenum foil is placed in a tubular furnace and heated to 700°C at a heating rate of 10°C / min in an air atmosphere for 120 minutes, and then a thick layer of three-dimensional molybdenum-based oxide structure is formed on the surface of the molybdenum foil.

[0098] Step 2: According to the principle of thermal reduction reaction, the three-dimensional molybdenum-based oxide prepared above is placed in a cleaned ceramic boat and placed in a tube furnace. Before heating the tube furnace, the tube furnace is first closed and evacuated to about 1 Torr, and then filled with argon to remove the residual gas in the quartz tube. Then the tube furnace is quickly heated to 600°C within 30 minutes and the reaction temperature is maintained for 30 minutes. During this annealing reduction process, a mixed gas of argon and hydrogen is always passed through with a flow rate of Ar:H 2 =60:40, and then naturally cooled to room temperature, and the obtained sample was molybdenum dioxide.

[0099] Step 3: Prepare the MoO 2 Place it in a cleaned ceramic boat, and place it downstream of the tube furnace. The ceramic boat loaded with 0.08g of red phosphorus is placed upstream of the tube furnace. Before heating the tube furnace, first close the tube furnace, evacuate it to about 1Torr, and then fill the tube furnace with argon to remove the residual gas in the quartz tube. Then quickly heat the tube furnace to 700℃ within 30min, and maintain the reaction temperature for 30min. During this phosphating process, a mixed gas of argon and hydrogen is always passed through with a flow rate of Ar:H 2 =60:40, and then cooled naturally to room temperature. The obtained sample is MoO 2 -MoP composite catalyst.

[0100] Example 5

[0101] Step 1: First, sand off the oxide layer on the surface of the molybdenum foil with sandpaper, and then place the polished molybdenum foil in hydrochloric acid and hot acetone (80°C) in turn, soak for 30 minutes to remove surface oil. After rinsing with deionized water, ultrasonic cleaning is performed in anhydrous ethanol for 30 minutes, and finally blown dry with a nitrogen gun for use. The dried molybdenum foil is placed in a tubular furnace and heated to 700°C at a heating rate of 10°C / min in an air atmosphere for 120 minutes, and then a thick layer of three-dimensional molybdenum-based oxide structure is formed on the surface of the molybdenum foil.

[0102] Step 2: According to the principle of thermal reduction reaction, the prepared three-dimensional molybdenum-based oxide is placed in a cleaned ceramic boat and placed in a tube furnace. Before heating the tube furnace, the tube furnace is first closed and evacuated to about 1 Torr, and then filled with argon to remove the residual gas in the quartz tube. Then the tube furnace is quickly heated to 800°C within 30 minutes and the reaction temperature is maintained for 30 minutes. During this annealing reduction process, a mixed gas of argon and hydrogen is always passed through with a flow rate of Ar:H 2 =60:40, and then naturally cooled to room temperature, and the obtained sample was molybdenum dioxide.

[0103] Step 3: Prepare the MoO 2Place it in a cleaned ceramic boat, and place it downstream of the tube furnace. The ceramic boat loaded with 0.08g of red phosphorus is placed upstream of the tube furnace. Before heating the tube furnace, first close the tube furnace, evacuate it to about 1Torr, and then fill the tube furnace with argon to remove the residual gas in the quartz tube. Then quickly heat the tube furnace to 700℃ within 30min, and maintain the reaction temperature for 30min. During this phosphating process, a mixed gas of argon and hydrogen is always passed through with a flow rate of Ar:H 2 =60:40, and then cooled naturally to room temperature. The obtained sample is MoO 2 -MoP composite catalyst.

[0104] Morphology analysis

[0105] The sample obtained in Example 1 was subjected to X-ray diffraction and field emission scanning electron microscopy structural analysis. The results are as follows: Figure 3 As shown, the sample has MoO 2 and MoP mixed phase. Figure 4 , through field emission scanning electron microscopy, we can see MoO 2 -MoP composite surface morphology. According to the X-ray photoelectron spectroscopy analysis results, Figure 5 As shown, it can be confirmed again that the sample is MoO 2 -MoP composite catalyst.

[0106] Analysis of electrocatalytic hydrogen evolution performance

[0107] The electrocatalytic hydrogen evolution performance of Example 1 was studied using a three-electrode system. Figure 8 As shown, the Ag / AgCl electrode (internal system electrolyte is saturated KCl solution) is used as the reference electrode, the platinum wire is used as the counter electrode, and the 0.5MH 2 SO 4 and 1.0M KOH as the electrolyte. The sample was cut into 1 cm × 1 cm size and directly used as the working electrode. It was fixed to the clip electrode (Pt sheet as the conductor) and then tested on the electrochemical workstation (CHI600E, Shanghai Chenhua Company). The test results in this study are based on the formula: E RHE =E Ag / AgCl +0.059×PH+0.198, respectively, to normalize the current density and potential value. Before the test, argon (Ar) was introduced into the electrolyte for half an hour to remove the adsorbed O 2 Then, the polarization curves were obtained by linear voltammetry with a scan rate of 5 mV / s and a scan range of 0 V to -1 V vs. RHE. All potentials in this work are described relative to the reversible hydrogen electrode (RHE).

[0108] Figure 7The lower electrode of Example 1 is shown in 0.5MH 2 SO 4 and 1M KOH. It is worth noting that these data are not compensated for internal resistance (iR), and the current is normalized to the electrode geometric area. Under alkaline conditions, MoO 2 -The initial hydrogen evolution potential of the MoP / Mo composite electrode is about -15mV, and the current density increases sharply with the increase of negative voltage, showing the best hydrogen evolution reaction activity. In addition, another important indicator for measuring the activity of electrocatalytic hydrogen evolution reaction is the cathode current density, which should reach 10mA / cm 2 ,MoO 2 -MoP / Mo composite electrode requires an overvoltage of 62mV. In sharp contrast, MoP and MoO 2 The overpotentials required by the materials are 231mV and 167mV respectively, which means that a larger overpotential is required to decompose water and produce hydrogen, indicating that its catalytic activity is significantly lower than that of MoO 2 -MoP / Mo composite electrode. In practical industrial applications, high current density is an important indicator for judging catalyst performance. At a high current density of 800mA / cm 2 ,MoO 2 The overpotential required for the MoP / Mo composite electrode is 378 mV, which is much smaller than 608 mV for the Pt / C electrode, indicating its superior catalytic performance.

[0109] Usually, the Tafel slope is used to show the kinetic information of hydrogen evolution reaction. Figure 8 As shown, where j is the current density (mA / cm -2 ), under alkaline conditions, MoO 2 -The Tafel slope of the MoP / Mo composite electrode is relatively small. In practical industrial applications, a lower Tafel slope is beneficial to the electrocatalytic hydrogen evolution reaction. As the voltage increases, the faster the current of the electrocatalyst with a lower Tafel slope increases, the higher the rate of hydrogen production from water decomposition. Therefore, MoO with a smaller Tafel slope is more likely to produce hydrogen. 2 -MoP / Mo composite electrode, showing the highest catalytic activity for hydrogen evolution reaction.

[0110] In addition to the electrocatalytic hydrogen evolution reaction activity, catalyst stability is another important factor that restricts its practical application. In order to study the stability of the catalyst, the current-time dependence curve (IT curve) of the electrode material is tested to evaluate the stability of the material. Fig. 9 As shown, MoO 2-After the MoP / Mo composite electrode was tested for 200 hours, its performance was slightly degraded. Then, we repaired the electrode again and its catalytic activity was restored. This shows that the electrode prepared by the present invention can be repeatedly repaired, thereby reducing the cost of electrode raw materials.

[0111] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a molybdenum-based composite material, characterized in that: The following steps are involved: (S1) Reaction I on molybdenum foil to obtain MoO3 film; (S2) After annealing and reducing MoO3, MoO2 is obtained; (S3) placing red phosphorus upstream of the circulating airflow and MoO2 downstream to react with II to obtain a MoO2-MoP / Mo composite material; The molybdenum-based composite material comprises MoO2, MoP and a Mo substrate; The MoO2 and the MoP are grown on the Mo substrate; The MoO2 and the MoP are layered structures; The conditions of reaction I in step (S1) are as follows: The insulation temperature is 650℃~700℃; The holding time is 30 min~120 min; The heating rate is 10 ℃ / min ~40 ℃ / min; The reaction atmosphere is an oxygen-containing atmosphere; The conditions for annealing reduction in step (S2) are as follows: The insulation temperature is 600℃~750℃; The insulation time is 30 min~60 min; The heating rate is 10 ℃ / min ~40 ℃ / min; The reaction atmosphere was a mixture of argon and hydrogen; The flow ratio of hydrogen and argon is 1:1~1:3; The conditions of reaction II in step (S3) are as follows: The insulation temperature is 500℃~900℃; The holding time is 10 min~60 min; The heating rate is 10 ℃ / min ~40 ℃ / min; The reaction atmosphere was a mixture of argon and hydrogen; The flow ratio of hydrogen and argon is 1:1~1:

3.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the MoO2 to the MoP is 9:1~1:

1.

3. The preparation method according to claim 1, characterized in that: The thickness of the Mo substrate is 0.1 mm to 1 mm.

4. The preparation method according to claim 1, characterized in that: The thickness of the Mo substrate is 0.15 mm to 0.25 mm.

5. The preparation method according to claim 1, characterized in that: The thickness of the MoO2 and the MoP is 10 μm to 30 μm.

6. The preparation method according to claim 5, characterized in that: The thickness of the MoO2 and the MoP is 15 μm to 20 μm.

7. The preparation method according to claim 1, characterized in that: The MoO3 film has a three-dimensional structure.

8. The preparation method according to claim 1, characterized in that: The mass of the red phosphorus is 0.05 g to 0.2 g.

9. The preparation method according to claim 1, characterized in that: Before annealing and reduction in step (S2), the vacuum is evacuated to 1 Torr~5 Torr, and then filled with argon gas.

10. The preparation method according to claim 1, characterized in that: Before reaction II in step (S3), evacuate to 1 Torr~5 Torr and then fill with argon.

11. Use of the molybdenum-based composite material obtained by the preparation method according to any one of claims 1 to 10 as a cathode catalyst for hydrogen evolution.

Citation Information

Patent Citations

  • Method for preparing nitrogen-doped molybdenum-based chalcogenide electrolysis water hydrogen evolution catalytic material

    CN111514916A

  • Method of preparing molybdenum dioxide or molybdenum thin film by hydrogen-reduction reaction of molybdenum oxide

    KR1020090069515A